Application of SonoVue combined with three-dimensional color power angiography in the diagnosis and prognosis evaluation of intrauterine adhesion. (March 2016) - Yan, Ling; Wang, Aiming; Bai, Ruifang; Shang, Wei; Zhao, Yong; Wang, Weizhou; Guo, Wei
Abstract: Objective: To investigate the significance of the related indexes of three-dimensional color power angiography (3D-CPA) combined with SonoVue angiography in the diagnosis and prognosis evaluation of intrauterine adhesion (IUA). Methods: The accuracy, sensitivity, and specificity were evaluated between 3D-TVS and hysteroscopy. Endometrial thickness, volume (V), mean gray value (MG), vascularization index (VI), flow index (FI), vascularization flow index (VFI), and other related indexes before and after the angiography were compared. According to the hysteroscopy findings, the patients were divided into three groups: mild, medium, and severe. The endometrial thickness at 3 months postoperatively and the pregnancy rates at 1 year postoperatively were compared. Results: Compared with the hysteroscopy, sensitivity: 0.970 (0.021), specificity: 0.667 (0.086), (the values inside the bracket were the standard error), positive likelihood ratio: 2.909, negative likelihood ratio: 0.045. There was a significant difference in endometrial thickness and V between the three groups ( P < 0.05), and there was a significant difference in MG, VI, FI, and VFI between the mild and severe group ( P > 0.05). During intravenous injection of SonoVue, the blood flow of each group increased ( P < 0.001), and the VI, FI, and VFI of each group were significantly different ( P < 0.05). Compared with the preoperative values, the endometrial thickness, V, MG, VI, FI, and VFI significantly changed at 3 months postoperatively ( P < 0.05). The mild group and high VI group had a higher pregnancy success rate at one year postoperatively. Conclusion: 3D-CPA can indirectly diagnose IUA, and may play an important role in prognosis assessment.